2015
DOI: 10.1016/j.intimp.2015.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated carbon dioxide on bronchial epithelial innate immune receptor response to organic dust from swine confinement barns

Abstract: Hypercapnia is known to have immunoregulatory effects within the lung. Cell culture systems demonstrate this in both macrophages and alveolar cell lines, suggesting that alveoli are affected by changes in CO2 levels. We hypothesized that hypercapnia would also modulate human bronchial epithelial cell immune responses. Innate immune responses to Pam3CSK4 (TLR2 ligand), LPS (TLR4 ligand) and a complex innate immune stimulus, an extract from the organic dust of swine confinement barns (barn dust extract or BDE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…1a), and a shift in the population from predominantly macrophages to predominantly neutrophils (Fig. 1b), as has been seen in previous studies [9, 24]. Additional exposure to elevated CO 2 conditions induced no discernable changes in either number or type of cells present in the alveolar space, both in saline as well as barn dust exposed animals, even when CO 2 was increased to 7500 ppm.
Fig.
…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…1a), and a shift in the population from predominantly macrophages to predominantly neutrophils (Fig. 1b), as has been seen in previous studies [9, 24]. Additional exposure to elevated CO 2 conditions induced no discernable changes in either number or type of cells present in the alveolar space, both in saline as well as barn dust exposed animals, even when CO 2 was increased to 7500 ppm.
Fig.
…”
Section: Resultssupporting
confidence: 84%
“…Given that elevation of other gasses in this environment showed potential to enhance lung inflammatory symptoms [18], that CO 2 could alter response to dust extract exposures in bronchial epithelial cells [24] and that levels as low as 1000 ppm were capable of inducing changes in cognitive function [25], we hypothesized that the elevation of CO 2 gas exposure may enhance the inflammatory response to HDE exposure. We therefore looked to see if there was any effect of CO 2 on HDE exposure at the Occupational Safety and Health Administration (OSHA) 8 h workplace permissible exposure limit of 5000 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, Schneberger et al . previously reported that hypercapnia reduced LPS-induced secretion of IL-6 and IL-8 in the airway epithelial cell line BEAS-2B 35 . These observations are relevant because of the well-documented role of TLR4 in host defense against multiple respiratory pathogens 36 40 .…”
Section: Discussionmentioning
confidence: 80%
“…RNA was isolated from the lung tissue using RNeasy mini kit (Qiagen, Valencia, CA) following manufacturer instructions as previously described [ 33 , 34 ]. After RNA isolation, the concentration and purity of RNA was determined by NanoDrop spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%